Customary Justice Model in Resolving Indigenous Conflicts in Merauke Regency Papua - Erni Dwita Silambi; Marlyn Jane Alputila; Syahruddin Syahruddin (Faculty of Law, Musamus University, 2018)
The background of the keyword is the agenda of customary justice in the government which is clearly burdened by rules that are recognized and carried out well, making it possible to provide recognition of the prevailing customs in the community. The